2016
DOI: 10.1155/2016/5303048
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Properties of Mesenchymal Stem Cells: Therapeutic Potential for Cystic Fibrosis Infection, and Treatment

Abstract: Cystic fibrosis (CF) is a genetic disease in which the battle between pulmonary infection and inflammation becomes the major cause of morbidity and mortality. We have previously shown that human MSCs (hMSCs) decrease inflammation and infection in the in vivo murine model of CF. The studies in this paper focus on the specificity of the hMSC antimicrobial effectiveness using Pseudomonas aeruginosa (gram negative bacteria) and Staphylococcus aureus (gram positive bacteria). Our studies show that hMSCs secrete bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
146
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(162 citation statements)
references
References 39 publications
8
146
1
1
Order By: Relevance
“…An in-vivo study on CF lung treated with hMSCs showed significant reduction in the bacterial infection and an increase in the production of antimicrobial peptide LL-37. hMSCs have the potential to increase the efficacy of antibiotics and decrease the bacterial growth by releasing soluble products [197]. In addition to the bronchial epithelial cells, nasal airway epithelial cells, intestinal organoids from intestinal stem cell biopsy, monocytes and macrophages have also been studied for CFTR therapy [198, 199].…”
Section: Discussionmentioning
confidence: 99%
“…An in-vivo study on CF lung treated with hMSCs showed significant reduction in the bacterial infection and an increase in the production of antimicrobial peptide LL-37. hMSCs have the potential to increase the efficacy of antibiotics and decrease the bacterial growth by releasing soluble products [197]. In addition to the bronchial epithelial cells, nasal airway epithelial cells, intestinal organoids from intestinal stem cell biopsy, monocytes and macrophages have also been studied for CFTR therapy [198, 199].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, current data suggest that MSCs exert strong antimicrobial effects through indirect and direct mechanisms (1626). Indirectly, across their role in the host immune response against pathogens, especially in the dynamic coordination of the pro- and anti-inflammatory elements of the immune system (22, 2729) or increasing the activity of phagocytes (18, 21, 25, 30, 31); and directly, by the secretion of antimicrobial peptides and proteins (AMPs) (19, 20, 23, 24, 26), and also by the expression of molecules such as indoleamine 2,3-dioxygenase (IDO) (16) and interleukin (IL)-17 (32). In fact, MSCs have been reportedly responsible of the bacterial clearance in preclinical models of sepsis (1720, 22, 25), acute respiratory distress syndrome (ARDS) (21, 26), and cystic fibrosis infection (23).…”
Section: Introductionmentioning
confidence: 99%
“…These molecules have selective activity against a wide range of organisms including bacteria, yeasts, fungi, viruses, and even cancer cells (34). So far, MSCs have been found to constitutively express four AMPs: cathelicidin LL-37 (19, 23), human β-defensin-2 (hBD-2) (24), hepcidin (20), and lipocalin-2 (Lcn2) (26), which can be further modulated during infection and inflammation. In fact, it has been demonstrated that, in MSCs, a bacterial preconditioning induces an upregulation of LL-37, hBD-2, and hepcidin (19, 20, 24), while their preconditioning with inflammatory stimuli evoke increasing levels of LL-37 and Lcn2 (23, 26).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Транзиторное воздействие TNFα, ЛПС или других лигандов TLR увеличивает остеогенез и зависит от дозы, времени и периода воздействия стимулов [13]. Однако, воздействие хронической воспалитель-ной среды вызывает активацию остеокластов и нарушение остеогенеза МСК и изменяет ба-ланс ремоделирования кости в сторону остеоли-тического процесса [54].…”
Section: роль мск в ремоделировании костной тканиunclassified